HUBUNGAN PENGEMBANGAN DIRI DENGAN LOYALITAS KINERJA GURU SEKOLAH DASAR - Astuti, Puji (Perspektif Ilmu Pendidikan, 2019)
This research aims to determine the correlation between self-development and teacher performance loyalty. This study was conducted in SDN 2 Margomulyo, OKU Timur with a total of 25 teachers. A cross-sectional design was used and implemented from April to August 2018. The data analysis technique used was nonparametric statistics. The results showed that there was no signifcant relationship between self-development with performance loyalty (0,877 > 0,05). Based on this result, implications and recommendations are discussed further. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">